Syndecan-4 negatively regulates antiviral signalling by mediating RIG-I deubiquitination via CYLD - Wei Lin (Nature Portfolio, 2016)
Syndecans are transmembrane proteoglycans implicated in diverse cellular activities. Here the authors show that Syndecan-4 via its cytosolic domain negatively regulates antiviral immunity by enhancing RIG-I interaction with a deubiquitinating enzyme CYLD, thus inhibiting the activating K63-linked RIG-I ubiquitination.